Ethnomedical Survey of Aborigines Medicinal Plants in Gua Musang, Kelantan, Malaysia - Hamzah, Nurraihana; Noor Azmi, Norfarizan Hanoon; Hasmah, A.; Norsuhana, A. H.; Fatan, H. Y. (School of Health Sciences, Universiti Sains Malaysia, 2016)
The practice of herbal medicine had been diminishing, which may lead to the loss of valuable information about healing herbs. Therefore, an ethnomedical analysis was carried out in order to document the traditional medicinal uses of plants, which are commonly used among the Kelantanese Aborigines. A detailed systematic exploration of traditional ethnobotanical knowledge of medicinal plants of rural area in Kelantan was carried out mainly through interviews among aboriginal households (house-to-house interviews) and traditional healers. A total of 46 species was identified as having potential medicinal efficacy in curing different diseases and illnesses. Findings from this study can be used as a pharmacological basis in selecting plants for further phytochemical and pharmaceutical-nutrition studies.